Three-dimensional boundary element assessment of a fibre/matrix interface crack under transverse loading - Cisilino, Adrian Pablo (2005)
The macroscopic behaviour of unidirectional fibre-reinforced-composite materials is strongly dependent on the strength of the fibre/matrix adhesion. The stress concentrations around the fibres lead to micro-crack initiation, which will grow along a ply to become a complete transverse crack. In this paper a boundary element methodology for the three-dimensional analysis of bimaterial interface cracks is presented. Fracture mechanics parameters, namely J-integral and stress intensity factors, are computed along the crack front using the Energy Domain Integral and the M1-integral methodologies. The devised numerical tool is employed to analyse the problem of a fibre/matrix interface crack under transverse loading in order to assess the three-dimensional character of the problem, and to evaluate the representatives of the results obtained from two-dimensional models. Obtained results show the key role played by the relative elastic properties of the fibre, the matrix and the laminate on the state of mixed mode fracture.